Water quality changes in acid mine drainage streams in Gangneung, Korea, 10 years after treatment with limestone - Shim, Moo Joon; Choi, Byoung Young; Lee, Giehyeon; Hwang, Yun Ho; Yang, Jung-Seok; O'Loughlin, Edward J.; Kwon, Man Jae (ELSEVIER SCIENCE BV, 2015)
To determine the long-term effectiveness of the limestone treatment for acid mine drainage (AMD) in Gangneung, Korea, we investigated the elemental distribution in streams impacted by AMD and compared the results of previous studies before and approximately 10 years after the addition of limestone. Addition of limestone in 1999 leads to a pH increase in 2008, and with the exception of Ca, the elemental concentrations (e.g., Fe, Mn, Mg, Sr, Ni, Zn, S) in the streams decreased. The pH was 2.5-3 before the addition of limestone and remained stable at around 4.5-5 from 2008 to 2011, suggesting the reactivity of the added limestone was diminished and that an alternative approach is needed to increase the pH up to circumneutral range and maintain effective long-term treatment. To identify the processes causing the decrease in the elemental concentrations, we also examined the spatial (approximately 7 km) distribution over three different types of streams affected by the AMD. The elemental distribution was mainly controlled by physicochemical processes including redox reactions, dilution on mixing, and co-precipitation/adsorption with Fe (hydr)oxides. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: DUCKTOWN MINING DISTRICT; HYDROGEOCHEMICAL CHARACTERISTICS; PASSIVE TREATMENT; DISSOLVED METALS; IMGOK CREEK; COAL-MINE; IRON; SEDIMENTS; SULFATE; ADSORPTION